(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
This article explores how the effectiveness of German lessons can be improved. It also describes innovative methods and ways of teaching German in lectures. In order to identify the essential components necessary for the implementation of this model of teaching students in a foreign language, the possibilities of expanding the powers of professors and teachers in matters of modern teaching methods are shown